Anti-Müllerian Hormone Trajectories Are Associated With Cardiovascular Disease in Women: Results From the Doetinchem Cohort Study. Issue 6 (7th February 2017) - de Kat, Annelien C.; Verschuren, W. Monique; Eijkemans, Marinus J.C.; Broekmans, Frank J.M.; van der Schouw, Yvonne T.
Abstract : Background: Earlier age at menopause is widely considered to be associated with an increased risk of cardiovascular disease. However, the underlying mechanisms of this relationship remain undetermined. Indications suggest that anti-Müllerian hormone (AMH), an ovarian reserve marker, plays a physiological role outside of the reproductive system. Therefore, we investigated whether longitudinal AMH decline trajectories are associated with an increased risk of cardiovascular disease (CVD) occurrence. Methods: This study included 3108 female participants between 20 and 60 years of age at baseline of the population-based Doetinchem Cohort. Participants completed ≥1 of 5 consecutive quinquennial visits between 1987 and 2010, resulting in a total follow-up time of 20 years. AMH was measured in 8507 stored plasma samples. Information on total CVD, stroke, and coronary heart disease was obtained through a hospital discharge registry linkage. The association of AMH trajectories with CVD was quantified with joint modeling, with adjustment for age, smoking, oral contraceptive use, body mass index, menopausal status, postmenopausal hormone therapy use, diastolic blood pressure, total cholesterol, high-density lipoprotein cholesterol, and glucose levels. Results: By the end of follow-up, 8.2% of the women had suffered from CVD, 4.9% had suffered from coronary heart disease, and 2.6% had experienced a stroke. After adjustment, each ng/mL lowerlog AMH level was associated with a 21% higher risk of CVD (hazard ratio, 1.21; 95% confidence interval, 1.07–1.36) and a 26% higher risk of coronary heart disease (hazard ratio, 1.25; 95% confidence interval, 1.08–1.46). Each additional ng/mL/year decrease oflog AMH was associated with a significantly higher risk of CVD (hazard ratio, 1.46; 95% confidence interval, 1.14–1.87) and coronary heart disease (hazard ratio, 1.56; 95% confidence interval, 1.15–2.12). No association between AMH and stroke was found. Conclusions: These results indicate that AMH trajectories in women are independently associated with CVD risk. Therefore, we postulate that the decline of circulating AMH levels may be part of the pathophysiology of the increased cardiovascular risk of earlier menopause. Confirmation of this association and elucidation of its underlying mechanisms are needed to place these results in a clinical perspective. Abstract : Supplemental Digital Content is available in the text.